Hubungan Berat Induk dan Berat Sapi Anak Sapi - Sulaiman Ibrahim (Jurnal Agripet, 2007)
ABSTRACT. A survey conducted to study a relationship between a dam body weight and a calf birth weight of cattle. There were six dams of Brahman Cross (B.C), six females calves of B.C dam, eleven local cattle dams and her eleven females calves, and another seven dams of local cattle and her seven male calves. The mean birth weight were local cattle and her seven male calves. The mean birth weight were 20.67 13.47 Kg for the female calf of B.C dam, and 19.27 4.41 Kg for thr female calf of local cattle dam, and 18 2.33 Kg for the male calf of local cattle dam. The mating method used was an artificial insemination and Brahman Cross frozen semen. The birth weight between the two groups of these female calves were not significantly different, and berween the two groubs of these female calves and the male calves were not significantly different. The body weights of B.C dams were not significantly correlated with their female calves ( r= + 0.7166, P0.05), and the local dam body weights were not significantly correlated with their female calves (r=+0.7450, P0.05), and with their male calves (r=+ 0.1948, P0.05). The equation of the regression lines were Y = 5.38 + 0.07 X for female calves and Y = 16.21 + 0.01 X for male calves. X dam body wight, and Y = calf birth weight.